Measuring Psychosocial Wellbeing in Democratic Republic of Congo - Horn, Rebecca (World Bank, Washington, DC, 2014)
Since it began operating in the 1990s in northern Uganda, the LRA has inflicted enormous suffering on millions of civilians in several countries of the Great Lakes and Central African regions. In the 1990s and early 2000s, suc¬cessive Ugandan People s Defense Force (UPDF) operations in northern Uganda largely drove the LRA into the DRC and what is now South Sudan, and after 2008, into the CAR. Armed conflict negatively affects women and men in different ways and results in gender-specific dis¬advantages which are not always recognized or ad¬dressed in mainstream conflict and reconstruction programs and policies. The Learning on Gender and Conflict in Africa Program (LOGiCA) aims to increase gender-specific programming in post-conflict Sub-Saharan Africa, with a focus on de¬mobilization and reintegration (D&R) in the Great Lakes region (GLR), and gender specific issues arising from armed conflict including psy¬chosocial aspects.